Determinar los efectos de diferentes dosis de los biofertilizantes MICRO-ASP y AZOSPITIC (Azospirillum brasilense) en el cultivo de ajonjoli - Ortega Nuñez, Edwin Leonardo (2017)
SUMMARY The investigation was carried out in the experimental farm of the Ability of Agricultural Sciences of the Technical University of Babahoyo, located in Km 7,5 of the road Babahoyo-Montalvo. Fourteen treatments and three repetitions were investigated. The objective was to evaluate the effect of different dose of the biofertilizantes MICRO-ASP and AZOSPITIC in the Sesamo cultivation, determining its effect on the grain yield. The variety Portoviejo-1 was sowed in parcels of 20 m2. The treatments were distributed at random in a design of complete blocks. For the evaluation of stockings the test was used from Tukey to significance 5 %. At the end of the cycle of the cultivation plant height was evaluated, days to flowering, number of capsules for plant, days to physiologic maturation, number of grains for capsule, weight of 10 capsules, yield for hectare and economic analysis. The results determined that applying the application of 80-30-60-15 kg/ha (N-P-K-S) more AZOSPITIC 1000 cc/ha (T7), it was achieved more capsules by plant (164,4 units), bigger yield for hectare (6,78 t/ha) and better economic utility ($ 4052,57). The treatment T11 (80-30-60-15 kg/ha (N-P-K-S) more AZOSPITIC 1500 cc/ha), it showed more grains for capsule (82,87), bigger weight of capsules (13,23 g) and it delayed more time in maturing.